Phytosociology and edaphic attributes of mangroves in Chettuwai backwater system, Thrissur, Kerala - Sindhumathi, S., Vidyasagaran, K., Gopakumar, S (INTERNATIONAL JOURNAL OF ENVIRONMENTAL SCIENCES, 2014)
A phytosociological and edaphic study was carried out in the mangroves of Chettuwai backwater system in Kerala. Floristic analysis revealed that the vegetation comprised of 12 mangrove species belonging to 10 families. Rhizophora mucronata reported maximum density and basal area, whereas, maximum frequency was observed in the case of Bruguiera cylindrica. The entire vegetation looked like a Rhizophora dominated community. The other floristic elements were represented by Avicennia officinalis, Bruguiera cylindrica, Aegiceras corniculatum, Acanthus illicifolius, Premna latifolia and Derris trifoliatum. Importance value index was maximum for Rhizophora mucronata. Simpson’s index of diversity was relatively low (0.54). Zonal distribution of plants was observed with respect to change in edaphic attributes. Soil was generally acidic in nature. Electrical conductivity and concentration of available P and K decreased down to the profile. Soil organic carbon and nitrogen did not vary significantly down to the profile. However, organic C and electrical conductivity showed significant variation between the zones. Potassium did not show significant variation between various zones studied.